A new species of Wiedemannia (Diptera: Empididae: Clinocerinae) from Balkan Peninsula - Ivković, Marija; Plant, Adrian; Horvat, Bogdan (Zootaxa, 2012)
Wiedemannia artemisa sp. nov. (Diptera: Empididae: Clinocerinae) is described from the Balkan Peninsula. Althoughcurrent subgeneric concepts are considered to have doubtful validity, the new species is tentatively assigned to the subgenus Philolutra Mik. The distribution of Wiedemannia in the Balkans is discussed.